Treatment Strategies for Genu Recurvatum in Adult Patients With Hemiparesis: A Case Series. Issue 2 (13th November 2014) - Appasamy, Malathy; De Witt, Michelle E.; Patel, Nisha; Yeh, Nancy; Bloom, Ona; Oreste, Anthony
Abstract: Objective: To report our clinical experience and propose a biomechanical factor–based treatment strategy for improvement of genu recurvatum (GR) to reduce the need for knee‐ankle‐foot orthosis (KAFO) or surgical treatment. Design: Case series. Setting: Outpatient clinic of a Department of Physical Medicine and Rehabilitation in an academic medical center. Subjects and Interventions: Adult subjects (n = 22) with hemiparesis and GR who received botulinum injections alone or in combination with multiple types of orthotic interventions that included solid ankle‐foot orthosis (AFO) ± heel lift, hinged AFO with an adjustable posterior stop ± heel lift, AFO with dual‐channel ankle joint ± heel lift, or KAFO with offset knee joint. Biomechanical factors reviewed included muscle strength, modified Ashworth score for spasticity, presence of clonus, posterior capsule laxity, sensory deficits, and proprioception. Outcome Measurements: Outcome factors were improvement or elimination of GR based on subjective assessment before and after the interventions by the same experienced clinician. Results: More than one biomechanical factor contributed to GR in all patients. Botulinum toxin A injection was used in patients who had significant plantar flexor spasticity and/or clonus. Four types of orthotic interventions were used based on the biomechanical factor: solid AFO in patients with severe ankle dorsiflexion and plantar flexion weakness or clonus; hinged ankle joint with adjustable posterior stop in patients with less severe ankle dorsiflexion weakness in the absence of clonus; AFO with a dual‐channel ankle joint for quadriceps weakness or severe proprioceptive deficits; and KAFO with offset knee joints in patients with Achilles tendon contracture or severe proprioceptive deficits. Adjunctive options included the addition of heel lifts and toeplate modifications. Combinatorial interventions of botulinum injection, modified AFOs, and heel lifts improved or eliminated GR and avoided the need for cumbersome orthotics or surgical interventions. Conclusions: GR in hemiparesis is multifactorial and can be successfully controlled by using a conservative biomechanical factor–based approach and combined medical and orthotic interventions. An algorithmic approach and a prospective study design is proposed to determine a combination of effective interventions to correct GR.